2013
DOI: 10.1589/jpts.25.1485
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Obesity on Fall Efficacy in Elderly People

Abstract: [Purpose] The aim of this study was to identify the effects of obesity on falls as a practical verification of the importance of obesity-targeting interventions as part of future fall prevention programs. [Subjects and Methods] The study involved 351 elderly people (172 men, 179 women) living in rural areas. The dependent variable, fall efficacy, was measured using the Falls Efficacy Scale, while the independent variables, body mass index (BMI) and visceral fat, were measured using the InBody 720. The Faces Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
3
19
0
1
Order By: Relevance
“…Corroborating the findings of the present study, Jeon et al 22 evidenced a relationship between BMI and fear of falling in a sample of 351 old Koreans; however, the risk of falls was not the aim of that study. Conversely, Mitchell et al 5 observed higher occurrence of falls in obese elderly, but the fear of falling did not differ among BMI strata.…”
Section: Discussionsupporting
confidence: 66%
“…Corroborating the findings of the present study, Jeon et al 22 evidenced a relationship between BMI and fear of falling in a sample of 351 old Koreans; however, the risk of falls was not the aim of that study. Conversely, Mitchell et al 5 observed higher occurrence of falls in obese elderly, but the fear of falling did not differ among BMI strata.…”
Section: Discussionsupporting
confidence: 66%
“…20,21 In our study we found that BMI and sex are the variables that have an independent effect on the dimensions foot function and general foot condition. Thus, we conclude that increasing BMI worsens the function of the foot, the general foot condition, and the social function of the person, negatively affecting the quality of life of the elderly.…”
Section: Discussionmentioning
confidence: 49%
“…Older adult women were more likely to fall than older adult men (19) . The fear of falling among older adult women was associated with reduced physical activity (19) ; obesity (20)(21) ; impairment of activities of daily living (ADLs) (19) ; social isolation (4) ; higher depressive symptoms (20,22) ; higher probability of future falls (23) . The fear of falling among older adult women is influenced by a number of factors peculiar to gender, such as a higher prevalence of chronic non-communicable diseases (NCDs) and musculoskeletal frailty (23) ; low bone density after menopause and greater and more rapid loss of muscle mass, due to the hormonal decrease (24) .…”
Section: Discussionmentioning
confidence: 99%